Clinical efficacy of combined therapy for perianal eczema caused by anal diseases in 160 cases - Zhi-Chao LIU; Jian-Gang LIU; Zhe LI; Qing SUN (Wolters Kluwer Medknow Publications, 2007)
Perianal eczema is a kind of inflammatory dermatosis on the perianal skin and mucosa. The aim of the study was to evaluate the clinical efficacy of the combined therapy of medicine and operation for the perianal eczema caused by the anal diseases such as hemorrhoids, fissures and fistulas. One hundred and sixty patients with perianal eczema were involved in this study. They were randomly divided into four groups and treated by different therapies for four weeks respectively. Group A (40 patients) was only treated with medicine, Group B (40 patients) only with operation, Group C (40 patients) firstly with medicine and then with operation and Group D (40 patients) firstly with operation and then with medicine. The efficacy was determined as reduction of lesion size relative to initial size. The cure rate was 22.50%, 32.50%, 57.50% and 45.00% in Group A, B, C and D, respectively. The effective rate was 40.00%, 52.50%, 85.00% and 75.00%, respectively. The efficacy was significantly different (H=20.8689, g = 3, P value =0.0001). The results of group comparison showed that there were significant difference between Group C and Group A, Group C and Group B, Group D and Group A (all P values, < 0.05). It was concluded that the combined therapy of medicine and operation is optimal choice for the perianal eczema caused by the anal diseases such as hemorrhoids, fissures, and fistula. It highly improves the cure rate and efficacy rate.